2011
DOI: 10.1143/jjap.50.094101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Electron Mobility in Accumulation-Mode Silicon-on-Insulator Metal–Oxide–Semiconductor Field-Effect Transistors

Abstract: Junctionless, or accumulation-mode, metal–oxide–semiconductor field-effect transistors (MOSFETs), where the channel and source/drain doping types are the same, have attracted growing interests because of their simpler fabrication processes. However, carrier transport properties, in particular, mobility characteristics, in the junctionless silicon-on-insulator (SOI) MOSFETs have been less studied. Although higher mobility in accumulation-mode SOI MOSFETs has been reported, the physical mechanisms of the higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In this paper, SOI MOSFETs with the same doping type for the channel as that for the source/drain are described as bodychannel SOI MOSFETs because electrons flow in the entire region of the SOI layer at the operation V g . [16][17][18][19] The phosphorus concentration in SOI is approximately 5 Â 10 15 cm À3 . T SOI is 150 nm.…”
Section: Device Structurementioning
confidence: 99%
“…In this paper, SOI MOSFETs with the same doping type for the channel as that for the source/drain are described as bodychannel SOI MOSFETs because electrons flow in the entire region of the SOI layer at the operation V g . [16][17][18][19] The phosphorus concentration in SOI is approximately 5 Â 10 15 cm À3 . T SOI is 150 nm.…”
Section: Device Structurementioning
confidence: 99%
“…Silicon-on-insulator (SOI) metal-oxide-semiconductor field-effect transistors (MOSFETs) have attracted much attention, because of their superior electrostatic characteristics, which are effective for suppressing short-channel effects (SCEs). [1][2][3] Three-dimensional-structure MOSFETs such as FinFETs and tri-gate FETs, where SOI substrates are utilized, are strong candidates for the 16 nm technology node and beyond. However, in SOI MOSFETs, the increased channel temperature (T ch ) may decrease the reliability of the device and worse mobility as well as the drain current (I d ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study,  e of greater than 1000 cm 2 V -1 s -1 is demonstrated, for the first time, in unstressed Si MOSFETs, where accumulation-mode, body-channel SOI MOSFETs are used [3][4][5]. It is revealed that worse  e in conventional inversion-mode Si MOSFETs is primarily due to larger D ac at Si/SiO 2 interface [6] as well as the larger form factor induced by quantum confinement in 2D electron system.…”
Section: Introductionmentioning
confidence: 77%